KAJIAN INFRASTRUKTUR PENGOLAHAN PERSAMPAHAN DI KOTA PEMANGKAT KABUPATEN SAMBAS - Walter, Denny (Jurnal Teknik Sipil, 2016)
The  fast  growing   level  people  for  city  will  make  more  burden  to  prepare  the  new infrastructure. One of the burden is some solid waste or commonly said garbage. When it is not well manage it will automatically reduce the quality of environment then will endanger the people themshelves.In line wit h the fast city growing and the social level of community and also the growing of the human technology, the garbage is seriur problem and it is needed the integrated, wise solution based on the new innovations, And it is must fulfill requirements from some aspects; socially, economically and also technically.People produce cheap garbagesin their daily life. Based on the survey and research done in the village of Penjajap, Pemangkat city, the amount of the garbage produced about0,736/kg/people/day. It consist of 62,288% of organic garbage and 37% of anorganic one. The common problem emerged when managing the garbage is operational technique and high cost. Most city in Indonesia are able to collect and dispose 60% from all the garbage production, and the rest is handled and discarded in unhygienic way and will contaminaaate the environment.